1992
DOI: 10.1139/g92-063
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic variation in rye regenerated plants and their progeny

Abstract: LINACERO, R., and VAZQUEZ, A. M. 1992. Cytogenetic variation in rye regenerated plants and their progeny. Genome, 35: 428-430. Regenerated plants obtained from immature embryo-derived.talluses of four cultivars of rye, as well as their progeny, were cytologically analyzed. Chromosome number modified plants were found among the regenerants. The progeny of apparently normal diploid regenerated plants was tested and in some cases chromosomally abnormal plants appeared. Equally, meiotic abnormalities were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For detailed description of the abbreviation see Fig 2. Materials with the same small letter (indicated on graph) of the given set belong to the same group (Miguel and Marum 2011). Such stress may cause the regeneration of the off-type plants that could be detected at the morphological (Li et al 2010), cytological (Linacero and Vazquez 1992), genetic or epigenetic level (Bednarek et al 2007;Vining et al 2013). Some of the changes may subsequently arise among progeny originated from tissue culture-derived regenerants even after many generative cycles (Bregitzer et al 1998;Kirikovich et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For detailed description of the abbreviation see Fig 2. Materials with the same small letter (indicated on graph) of the given set belong to the same group (Miguel and Marum 2011). Such stress may cause the regeneration of the off-type plants that could be detected at the morphological (Li et al 2010), cytological (Linacero and Vazquez 1992), genetic or epigenetic level (Bednarek et al 2007;Vining et al 2013). Some of the changes may subsequently arise among progeny originated from tissue culture-derived regenerants even after many generative cycles (Bregitzer et al 1998;Kirikovich et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture induced variation (TCIV) in regenerants (Li et al 2007;González et al 2013) and somaclonal variation (SV) in progeny of such regenerants (Linacero and Vazquez 1992;Ivanov et al 1998) have been observed in crops. TCIV may be manifested at the morphological level of regenerants (Jaligot et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Culture conditions may increase sensitivity of heterochromatic regions in regenerated DH plants for such breaks (Youssef et al 1989). Similar and other chromosomal structural modifications has been mentioned in anther derived plants of many crops such as barley (Mix et al 1978), rice (Mercy andZapata 1986, Mezencev et al 1995), maize (Ting 1985, Lee andPhillips 1987), rye (Linacero and Vazquez 1992) and cabbage (Chiang et al 1989). Plants carrying chromosomal abnormalities are a main source of male-sterility and cytological instability which usually impact the whole breeding program.…”
Section: Category Iii: R2-generationmentioning
confidence: 70%
“…Chromosome breakage in regenerants of cv. Ailés has been reported previously (Linacero & Vazquez, 1992).…”
Section: Discussionmentioning
confidence: 87%
“…There have been previous studies describing somaclonal variation in 'standard' outbred rye (e.g. Linacero & Vazquez, 1992). The aim of our study was not to make any direct comparisons between the inbred and outbred lines, but to investigate how the genetic make-up of the donor material influences the outcome in terms of somaclonal variation released.…”
mentioning
confidence: 99%